MnCo2O4-rGO Hybrid Magnetic Nanocomposite Modified Glassy Carbon Electrode for Sensitive Detection of L-Tryptophan. Issue 10 (1st January 2019) - Rebekah, A.; Kokulnathan, Thangavelu; Wang, Tzyy-Jiann; Viswanathan, C.; Ponpandian, N.
Abstract : The present work reports a highly sensitive electrochemical sensor based on manganese cobaltite entrapped reduced graphene oxide (MnCo2 O4 -rGO) modified glassy carbon electrode (GCE) for the efficient determination of tryptopan (Trp). The MnCo2 O4 -rGO nanocomposite was prepared by simple hydrothermal method. As synthesized nanocomposite was systematically characterized by using X-ray diffraction, Fourier-transform infrared spectroscopy, field emission scanning electron microscopy with energy dispersive X-ray analysis and elemental mapping. The electrocatalytic activities of Trp on MnCo2 O4 -rGO modified GCE were investigated using cyclic voltammetry and amperometry techniques. Under optimum experimental conditions, the MnCo2 O4 -rGO modified GCE exhibited good electrocatalytic performance such as wide linear range from 0.004 to 112.88 μM with a low detection limit of 1.0 nM (S/N = 3) and sensitivity of 5.195 μA μM −1 cm 2, respectively. Moreover, the proposed sensor showed an excellent anti-interference ability, good reproducibility, repeatability and stability. In addition, MnCo2 O4 -rGO/GCE was successfully applied for determination of Trp in food samples with satisfying recoveries using the standard addition method.